Decision and Game Theory for Security Second International Conference, GameSec 2011, College Park, MD, Maryland, USA, November 14-15, 2011. Proceedings - Baras, John S.; Katz, Jonathan; Altman, Eitan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the Second International Conference on Decision and Game Theory for Security, GameSec 2011, held in College Park, Maryland, USA, in November 2011. The 16 revised full papers and 2 plenary keynotes presented were carefully reviewed and selected from numerous submissions. The papers are organized in topical sections on attacks, adversaries, and game theory, wireless adhoc and sensor networks, network games, security insurance, security and trust in social networks and security investments.
Keywords: Computer science; Computer Communication Networks; Data protection; Computer software; Information Systems; Mathematics; Computer Science; Information Systems Applications (incl. Internet).; Computer Communication Networks; Systems and Data Security; Algorithm Analysis and Problem Complexity; Management of Computing and Information Systems; Game Theory, Economics, Social and Behav. Sciences